Construcción de un banco de prácticas para alineación de ejes en máquinas rotativas para los laboratorios de la universidad Antonio Nariño sede Cúcuta (2020)
In the integral work of degree the construction and assembly of a didactic bench for practices of alignment of axes of rotating machines and the elaboration of a laboratory guide to reinforce and complement the theoretical and practical knowledge of students in technological and engineering training are presented. Electromechanics of the Antonio Nariño University. The different methods of alignment on machine axes, identification of faults, rework costs and losses due to unscheduled operational stops are specified. The respective recommendations are made in the maintenance processes applied in the industry. The manufacturing process of the metal structure that supports the pump and motor assembly is detailed, which is used for the process of alignment practices in the laboratory. The schematic design of the didactic bench was carried out using SOLIDWORKS software.